Milestone - based assessment: an alternative continuous assessment strategy for laboratory learning outcomes - Lindsay, Euan (CQUniversity, 2008)
Engineering programs often feature units that contain a semester-long laboratory project, in which students complete an extended piece of work throughout the full duration of the semester. This paper presents an alternative assessment approach called “Milestone-Based Marking”. As students make incremental progress they can claim incremental marks, and are able to receive incremental feedback on their progress. Each of the milestones is rated for difficulty – Easy, Standard, Hard or Challenging. Easy milestones require less effort than Hard milestones, providing students with a clear guide as to how best to invest their time and effort. This approach changes the nature of the assessment from a purely summative process to a largely formative process. This approach has been used successfully across a number of units, with students indicating that they believe that the approach is fair, and that it better supports their learning.